Adsorption behavior and performance of ammonium onto sorghum straw biochar from water - Xu, Huajie; Wang, Bing; Zhao, Ruohan; Wang, Xiangui; Pan, Changbin; Jiang, Yuting; Zhang, Xueyang; Ge, Banggui (Scientific reports, 2022)
Sorghum has been widely used for liquor production and brewing, but how to make efficiently utilize sorghum straw (SS) has become an urgent problem. Meanwhile, the wastewater produced by winemaking is typical organic wastewater with a high ammonium concentration. To solve the problem of resource utilization of SS and remove ammonium from water, SS was used to prepare biochar as an adsorbent for ammonium adsorption. Batch adsorption experiments were carried out to study the influencing factors and adsorption mechanisms of ammonium onto sorghum straw biochar (SSB). The results showed that the adsorption capacity of SSB was much higher than that of SS. The SSB pyrolyzed at 300 °C had the highest adsorption capacity. The favorable pH was 6–10, and the optimal dosage was 2.5 g/L. The adsorption process and behavior conformed to the pseudo-second-order kinetic and Langmuir isotherm adsorption models. The maximum ammonium adsorption capacity of SSB at 45 °C was 7.09 mg/g, which was equivalent to 7.60 times of SS. The ammonium adsorption of SS and SSB was mainly chemical adsorption. The regeneration test indicated that SSB had good regeneration performance after three adsorption-regeneration cycles. This work suggests that SSB could be potentially applied to sewage treatment containing ammonium to achieve the purpose of resource recycling.